2015
DOI: 10.4269/ajtmh.15-0031
|View full text |Cite
|
Sign up to set email alerts
|

Differential Clinical Outcome of Dengue Infection Among Patients With and Without HIV Infection: A Matched Case–Control Study

Abstract: . This is mainly due to severe plasma leakage and the lack of hemorrhagic manifestations. Hospitalization duration was longer for DENV-HIV patients (10.5 days; interquartile range [IQR] = 5.5-26.3 days) compared with dengue patients (5 days; IQR = 4-6 days). There were no significant differences in presentation of clinical warning signs and symptoms at admission and during hospitalization, except for rash (adjusted COR [ACOR] = 0.06; 95% CI = 0.03-0.92). DENV-HIV patients were associated with higher pulse rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…To date, six clinical reports have described the clinical presentations of dengue infection in HIV-1-infected patients. [8][9][10][11][12][13] These reports suggest that HIV/DENV coinfection results in a benign clinical progression of dengue disease, as well as suppression of HIV-1 replication during the acute phase of dengue infection. [8][9][10] Here in we report a case of DENV-1 infection in an HIV-1-positive patient chronically infected with HBV in Colima State, Mexico, an endemic tropical region for DENV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…To date, six clinical reports have described the clinical presentations of dengue infection in HIV-1-infected patients. [8][9][10][11][12][13] These reports suggest that HIV/DENV coinfection results in a benign clinical progression of dengue disease, as well as suppression of HIV-1 replication during the acute phase of dengue infection. [8][9][10] Here in we report a case of DENV-1 infection in an HIV-1-positive patient chronically infected with HBV in Colima State, Mexico, an endemic tropical region for DENV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hotzz et.al., reported that DENV infection in ART-treated HIV patients was associated with reduced vascular instability and liver damage 26 . However, coinfected patients could have severe dengue outcomes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of these infections on the outcome of HIV infection is not well determined (11) . DENV infection causes a transient reduction in HIV load, apparently without impact on the clinical outcome of dengue fever or AIDS (12) . However, there is no information about the interaction of HIV with other arboviruses.…”
Section: Discussionmentioning
confidence: 99%